Brain oxygen extraction and neural tissue susceptibility are associated with cognitive impairment in older individuals. Issue 4 (16th March 2022) - Chiang, Gloria C.; Cho, Junghun; Dyke, Jonathan; Zhang, Hang; Zhang, Qihao; Tokov, Michael; Nguyen, Thanh; Kovanlikaya, Ilhami; Amoashiy, Michael; de Leon, Mony; Wang, Yi
Abstract: Background and Purpose: We investigated the effects of aging, white matter hyperintensities (WMH), and cognitive impairment on brain iron levels and cerebral oxygen metabolism, known to be altered in Alzheimer's disease (AD), using quantitative susceptibility mapping and MR‐based cerebral oxygen extraction fraction (OEF). Methods: In 100 individuals over the age of 50 (68/32 cognitively impaired/intact), OEF and neural tissue susceptibility (χn ) were computed retrospectively from MRI multi‐echo gradient echo data, obtained on a 3 Tesla MRI scanner. The effects of age and WMH on OEF and χn were assessed within groups, and OEF and χn were assessed between groups, using multivariate regression analyses. Results: Cognitively impaired subjects were found to have 19% higher OEF and 34% higher χn than cognitively intact subjects in the cortical gray matter and several frontal, temporal, and parietal regions ( p < .05). Increased WMH burden was significantly associated with decreased OEF in the cognitively impaired, but not in the cognitively intact. Older age had a stronger association with decreased OEF in the cognitively intact group. Both older age and increased WMH burden were significantly associated with increased χn in temporoparietal regions in the cognitively impaired. Conclusions: Higher brain OEF and χn in cognitively impaired older individuals may reflect altered oxygen metabolism and iron in areas with underlying AD pathology. Both age and WMH have associations with OEF and χn but are modified by the presence of cognitive impairment.